IMPROVING THE WORK OF MAINTAINING THE BALANCE OF REAL ESTATE OBJECTS IN SETTLEMENTS" (AS AN EXAMPLE OF BUILDINGS AND STRUCTURES IN THE CITY OF SAMARKAND (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Here are some key principles to guide the development of a robust system for managing real estate in Samarkand, focusing on its unique historical and cultural context.